Ibn Rushd and the “only materialist tradition” - Aguayo Bórquez, Claudio (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
The purpose of the present essay is to explore the possible relationship between Ibn Rushd’s thought, particulary his critic of traditional theologic kwnoledge and his theory of social body, with the concept of “only materialist tradition”, also called undercurrent of the materialism of encounter. For that, we confront Althusser’s theory of materialism whit those authors that Althusser considered as part of this “undercurrent” (especially Machiavelli, one of the most important names for this hypothesis of “history” of thought), and the Ibin Rushd’s problematic of body, public space and the confrontation with theology and pastoral power of his days, especially the Ashari theology.
Keywords: Materialist tradition; undercourrent of the materialism of encounter; imagination; democracy of relvelation; social body; medical methafor